Analysis of grouper business development in Gerokgak District, Buleleng Regency, Bali Province - David Hermawan; Ganjar Adhywirawan Sutarjo; Abdul Aziz (Universitas Muhammadiyah Malang, 2019)
Fisheries development is a human effort in increasing the utilization of all fishery's biological resources which include the fishery capture, aquaculture, and processing sectors. Grouper is a commodity that has high economic value, but the amount of aquaculture production is still low, one of which is in Gerokgak district.This research was conductedfrom February to March 2018, in Gerokgak District, Buleleng Regency,Bali Province. Dataobtainedthrough interviews, observations, documentation, and questionnaires directly with respondents, namely the Department of Maritime Affairs and Fisheries of Buleleng Regency, business owners, managers, and grouper farmers. The analysis used in this study was toobtaina grouper cultivation strategy using a SWOT analysis. From the results of the calculation of the analysis and determination of the SWOT matrix,thewgovernment must increase grouper aquaculture results by increasing the number of hatchery and enlargement businesses. The government is more responsive to the problems faced by farmers.